Exchange rate volatility and euro area imports - Robert Anderton; Frauke Skudelny (European Central Bank (ECB), 2001)
This paper estimates an import demand function for the euro area vis–vis its main extra-area trading partners which takes into account the possible impact of both intra- and extra-euro area exchange rate uncertainty. We derive a theoretical model which captures various mechanisms by which exchange rate volatility may influence the demand for extra-euro area imports. If importers are risk averse, the model predicts not only a negative effect of exchange rate volatility, but also substitution possibilities between extra- and intra-area imports due to differences in the degree of extra- and intra-area exchange rate volatility. The magnitude of these impacts also depends on the share of trade invoiced in foreign currency (and not hedged) as well as the degree of substitutability between the imports of different suppliers. Using quarterly data for the past eleven years, panel estimates suggest that extra-area exchange rate volatility may have decreased extra-euro area imports by around 10 per cent. Although such quantitative estimates should be treated with caution, the magnitude of our estimate is similar to other studies which find a statistically significant impact of exchange rate volatility on trade flows. Finally, we also provide some limited evidence that differences in extra- and intra-area exchange rate volatility may have resulted in substitution between extra- and intra-area imports.
Keywords: F15; F31; 330